Tuberculosis Diagnostics and Localization in Chest X-Rays via Deep Learning Models - Guo, Ruihua; Passi, Kalpdrum; Jain, Chakresh Kumar (Frontiers in Artificial Intelligence, 2020)
For decades, Tuberculosis (TB), a potentially serious infectious lung disease, continues to be a leading cause of worldwide death. Proven to be conveniently efficient and cost-effective, chest X-Ray (CXR) has become the preliminary medical imaging tool for detecting TB. Arguably, the quality of TB diagnosis will improve vastly with automated CXRs for TB detection and the localization of suspected areas, which may manifest TB. The current line of research aims to develop an efficient computer-aided detection system that will support doctors (and radiologists) to become well informed when making TB diagnosis from patients’ CXRs. Here, an integrated process to improve TB diagnostics via Convolutional Neural Networks (CNNs) and localization in CXRs via deep-learning models is proposed. Three (3) key steps in the TB diagnostics process include: (a) modifying CNN model structures; (b) model fine-tuning via artificial bee colony algorithm; and (c) the implementation of linear average based ensemble method. Comparisons of the overall performance are made across all three steps among the experimented deep CNN models on two publicly available CXR datasets, namely, the Shenzhen Hospital Chest X-Ray dataset and the NIH Chest X-Ray dataset. Validated performance includes detecting CXR abnormalities and differentiating among seven (7) TB-related manifestations (Consolidation, Effusion, Fibrosis, Infiltration, Mass, Nodule, and Pleural Thickening). Importantly, class activation mapping (CAM) is employed to inform a visual interpretation of the diagnostic result by localizing the detected lung abnormality manifestation on CXR. Compared to the state-of-the-art, the resulting approach showcases an outstanding performance both in the lung abnormality detection and the specific TB-related manifestation diagnosis vis-à-vis the localization in CXRs.